Analisis Pengaruh Peringkat Asia Sustainability Reporting Rating, Corporate Risk, Firm Size dan Profitabilitas terhadap Risiko Investasi Saham - Febriani, Nova (Universitas Darwan Ali, 2025)
This study examines the influence of the Asia Sustainability Reporting Rating (ASRRAT), corporate risk, firm size, and profitability on investment risk. The population in this study consists of companies listed in the SRI-KEHATI Index. The research sample was selected using a purposive sampling technique, comprising 15 companies. The study was conducted over the period from 2021 to 2023. This study used panel regression as the data analysis technique. The results show that ASRRAT ratings and profitability do not affect investment risk. In contrast, corporate risk has a positive effect, whereas firm size has a negative effect on investment risk.